(untitled) (African Journal of Biomedical Research, 2019)
The unconfirmed perception of herbal-based alcoholic beverages as drinks of medicinal, antimalarial and aphrodisiac value have resulted in increased intake of thwisese products in many developing countries. Herein, we investigated biochemical and physiological responses in rats of some commonly consumed herbalized alcoholic beverages in Nigeria. Male Wistar rats were treated with Action bitters (AcB), Alomo bitters (ALB), Origin bitters (OrB), 1960 bitters, Local gin (LG), Local gin plus Vitamin B (LG+VtB) daily at a dose of 2.68 mL/kg bw. A control group was given distilled water. Serum biochemical parameters; cholesterol, triacylglycerol, high and low density lipoprotein (H-LDL), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), gamma-glutamyl transferase (GGT) and electrolytes; potassium (K+), sodium (Na+), chloride (Cl-) and bicarbonate (HCO3-) were measured after 90 days treatment. There were significant increases in serum cholesterol, triacylglycerol, H-LDL, AST, ALT, ALP, LDH and GGT in alcohol treated groups compared with control suggesting hepato-toxicity. The Levels of (K+), sodium (Na+), and bicarbonate (HCO3-) significantly decreased in treatments groups compared with control indicating negative physiological consequences on serum electrolytes including hypokalemia, hyponatremia and osmotic balance. Principal component analysis (PCA), revealed a positive relationship between LG treatment group with cholesterol, triacylglycerol, AST, ALT, ALP, GGT, and LDH) indicating that LG induced more pronounced biological effects compared with other tested alcoholic beverages. Overall, the increase in cholesterol, triacylglycerol and LDL with a corresponding decrease in HDL in treatment groups compared with control may suggest a probable mode of action and provide a mechanistic insight by which alcoholic beverages induce coronary liver and heart disease.